ANALISIS KEPUASAN PELANGGAN TERHADAP KUALITAS LAYANAN KOPI KENANGAN - Dina Sintya Situngkir; Maretha Mariana Sembiring; Claudya Putri Br Sembiring; Yogen Agietha Tarigan (PT. Saha Kreasi Indonesia, 2025)
The development of the fast-food beverage industry in Indonesia has shown very rapid growth with a significant increase over time. This growth is supported by the increasing demand from the public for practical, ready-to-drink beverages that are easy to consume and offered at affordable prices. Indonesia is also known as a country with a rapidly growing logistics, food, and beverage sector, as evidenced by the increasing number of businesses in these industries. One of the most popular local coffee shops in Indonesia is Kopi Kenangan. This brand has become one of the fastest-growing local coffee brands, successfully expanding its reach nationwide, and focusing on the food and beverage sector by offering a variety of coffee products.This study employs a qualitative approach using interviews as the main data collection technique. The purpose of this research is to analyze the influence of positional advantage, promotion perception, and customer satisfaction on repurchase intention. The research population consists of Kopi Kenangan consumers in Medan City, with a sample of five respondents. The sampling criteria were determined based on consumers who have purchased Kopi Kenangan products at least twice. The results of the study indicate that purchase decisions are influenced by several complex factors, including consumer behavior, pricing, and the quality of service provided.